The protective function of personal growth initiative among a genocide-affected population in Rwanda - Blackie, Laura E.R.; Jayawickreme, Eranda; Forgeard, Marie, J.C.; Jayawickreme, Nuwan (American Psychological Association, 2015)
The aim of the current study was to investigate the extent to which individual differences in personal growth initiative (PGI) were associated with lower reports of functional impairment of daily activities among a genocide-affected population in Rwanda. PGI measures an individual’s motivation to develop as a person and the extent to which he or she is active in setting goals that work toward achieving self-improvement. We found that PGI was negatively associated with functional impairment when controlling for depression, posttraumatic stress disorder, and other demographic factors. Our results suggest that PGI may constitute an important mindset for facilitating adaptive functioning in the aftermath of adversity and in the midst of psychological distress, and as such they might have practical applications for the development of intervention programs.